PSYCHIC SUFFERING AS AN EXISTENTIAL POSSIBILITY: INEVITABILITY AND HUMAN FREEDOM IN VIKTOR FRANKL (PRÁXIS EM SAÚDE, 2025)
This study analyzes inevitable psychological suffering in the light of Logotherapy and Phenomenology, understanding it as a legitimate and inevitable part of human existence. The objective is to reflect on how psychological suffering, when welcomed with freedom and responsibility, can be reinterpreted and transformed into a source of meaning. The methodology adopted was a qualitative bibliographic review, based on authors who discuss the experience of suffering, psychopathology and the search for meaning. The results show that psychological suffering should not be reduced to a symptom or diagnosis, but recognized as an existential phenomenon that calls the subject to action and self-reconstruction. Logotherapy proposes an ethical and humanizing listening, which legitimizes pain without pathologizing it. It is concluded that, even in adversity, it is possible to reaffirm inner freedom, find meaning and sustain human dignity.
Keywords: Logotherapy; Psychic Suffering; Phenomenology; Freedom; Diagnosis